2022
DOI: 10.3390/admsci12010032
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure and Subjective Well-Being from a Gender Perspective

Abstract: Mainstreaming gender analysis into all aspects of policy making, including infrastructure and economic policy, is a key aspect to achieving gender equality. The main objective of this paper is to examine the impact of several public infrastructures on well-being by gender, applying the Capability and Subjective Well-being approaches. An index of access to infrastructure is constructed and its effect on well-being is estimated using a new survey dataset from Spain. The results from the logistic regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Van Eldijk and Gil (2020) also concluded that urban infrastructure projects displaced women and reduced their accessibility to economic hubs. Alarcón-García et al (2022) and Parikh et al (2015) concur, arguing that accessibility of transport infrastructure equalises gender capabilities, functioning and ultimately, female wellbeing. They argue that all dimensions of infrastructure are crucial for female wellbeing.…”
Section: Transport Infrastructure and Gender Inequalitymentioning
confidence: 98%
“…Van Eldijk and Gil (2020) also concluded that urban infrastructure projects displaced women and reduced their accessibility to economic hubs. Alarcón-García et al (2022) and Parikh et al (2015) concur, arguing that accessibility of transport infrastructure equalises gender capabilities, functioning and ultimately, female wellbeing. They argue that all dimensions of infrastructure are crucial for female wellbeing.…”
Section: Transport Infrastructure and Gender Inequalitymentioning
confidence: 98%
“…This paper selected the Haidian District, Chaoyang District, Dongcheng District, Xicheng District, and Fengtai District as study areas, which have a high degree of homogeneity in the built environment. In terms of community selection, combining previous studies and the original intentions of Beijing community construction [40,[42][43][44][45][46][47][48][49], Beijing communities are divided into old communities, company housing communities, policy housing communities, and new commercial housing communities, as shown in Table 1. This study randomly selects four types of communities from each administrative district.…”
Section: Study Areamentioning
confidence: 99%
“…Previous designs of existing community-built environments, which are based on an intensive treatment of land and high-density land use development, lead to a more diverse population inhabiting these spaces during urbanization [41]. Research on the factors affecting residents' subjective well-being at the community level mainly includes neighborhood relations [42], building quality [43], human-environment relations, landscape quality [44][45][46], infrastructure elements [47], convenient production, and consumption elements [48,49]. Some researchers have begun to further consider the types of communities.…”
Section: Introductionmentioning
confidence: 99%